2010
DOI: 10.1080/02786826.2010.507612
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Active Chlorine Oxidants in Saline-Oxone Aerosol

Abstract: The application of oxidative reactions of Oxone R [2KHSO 5 KHSO 4 K 2 SO 4 ] as an active decontaminant has been mainly utilized through the aqueous solution. However, little is known about reactivity of aerosolized Oxone particles although the use of appropriate aerosolized oxidants would have significant value in remediating contaminated surfaces. In this study, the feasibility of producing active chlorine species from saline-Oxone aerosols was studied using a 2-m 3 Teflon film chamber. To evaluate the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…FTIR spectra of aerosols on the disk were obtained under varying relative humidity from 10 to 85 %. Detailed descriptions of the methods can be found in the previous study by Jang et al (2010). Particle concentrations and particle size distributions were monitored continuously using a scanning mobility particle sizer (model 3080, TSI Inc.) together with a condensation nuclei counter (model 3025A, TSI Inc.…”
Section: Wood Smoke Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR spectra of aerosols on the disk were obtained under varying relative humidity from 10 to 85 %. Detailed descriptions of the methods can be found in the previous study by Jang et al (2010). Particle concentrations and particle size distributions were monitored continuously using a scanning mobility particle sizer (model 3080, TSI Inc.) together with a condensation nuclei counter (model 3025A, TSI Inc.…”
Section: Wood Smoke Characterizationmentioning
confidence: 99%
“…To investigate the hygroscopicity of wood smoke particle, the water content of the particle was monitored using the FTIR equipped with a miniature flow chamber under varying RHs (Jang et al, 2010). The absorbance at 1650 cm −1 , which is the characteristic frequency for O-H bending of water, was used to estimate the water content in the aerosol.…”
Section: Hygroscopic Properties Of Wood-burning Aerosolmentioning
confidence: 99%
“…ATD contains hygroscopic inorganic salts that form the thin water film on the surface of ATD particles when the salts are deliquescent (or above ERH). Some salts such as magnesium sulfate and calcium sulfate can be hydrated even at low humidity (Beardsley et al, 2013;Jang et al, 2010). Gustafsson et al (2005) reported that ATD particles showed a substantially high affinity to water compared to pure CaCO 3 particles.…”
Section: Gas-dust Particle Partitioningmentioning
confidence: 99%
“…Madison, WI, USA) interfaced with a specifically fabricated optical flow chamber by controlling the relative humidity in the range from 0.1 to 0.8. Humidity was controlled by combining humid air from a water bubbler and dry air from a dry air tank (Jang et al, 2010;Beardsley et al, 2013;Zhong and Jang, 2014). Calibration curves for water content (Mwall-water, mg m -3 ) of OMwall were obtained by the same method as Jang et al (2010).…”
Section: Hygroscopicity Of Omwallmentioning
confidence: 99%
“…Humidity was controlled by combining humid air from a water bubbler and dry air from a dry air tank (Jang et al, 2010;Beardsley et al, 2013;Zhong and Jang, 2014). Calibration curves for water content (Mwall-water, mg m -3 ) of OMwall were obtained by the same method as Jang et al (2010). The FTIR absorbance of the water peak (Abswater, 3350 cm -1 ) at different RH and the water mass fraction predicted from an inorganic thermodynamic model were related to determine the calibration curve.…”
Section: Hygroscopicity Of Omwallmentioning
confidence: 99%